MANSUR HALLAJ AND HIS IDEAS IN AHMAD YASSAVI’S WORKS - Amonova, Zilola (FILOLOGIYA UFQLARI JURNALI, 2024)
In the classical literature ot the East, various controversial ideas about Mansur Halloj and his idea o f "Anal haq" (Anal Truth) are widespread. The stones about Hallaj are given in the works o f Fa rididdin Attor, Jaloliddin Ruiri, Alisher Navoi. In addition, many artists were inspired f y the idea o f Hallo) and quoted his name and idea in their poors. In particular, this situation is reflected in the work o f Ahmad Kassa vi. The article analyzes Yassavi's wisdomabout Mansur 1 lalloj mid his idea of"Anal Truth", It is worth irentioniig tint the S u f poet also rrentioned the name o f Hallaj in his proverbs related to the evolution o f youth and expressed his views. In covering this issue, attcriion is paid to Ahirad Yassavi's contribution to the dodopnnnt o f the genie o f wisdoip his unique style and artistic skills, unlike other poets. The study used analytical and coirpara five methods.